Bath temperature role in tailoring the properties of chemically bath deposited tin sulfide films. (December 2022) - Khan, Nauman; Saleem, Muhammad Waqas; Javed, A.; Bashir, M.; Bashir, S.; Zeeshan, M.
Abstract: In this paper, the structural, optical and electrical properties of tin sulfide thin films are reported. Thin films are deposited (at different bath temperatures) by chemical bath deposition to investigate the role of bath temperature on the film properties. X-ray diffraction patterns reveal the structural phase transition from cubic to orthorhombic at 75 ºC bath temperature. FTIR spectra of cubic and orthorhombic films confirm dominant bond stretching of sulfur (S) and tin (Sn) atoms. Films deposited at different bath temperatures exhibit homogeneous and uniform surface morphology with surface roughness ≤ 45 ± 3 nm. Optical characterization shows that the cubic phase films have direct energy band gap ( E g ) which is observed to be decreased (2.20 eV to 1.76 eV) with increasing bath temperature (55 ºC to 65 ºC). At 75 ºC bath temperature, the obtained film crystallizes in orthorhombic crystal structure and has an indirect optical energy band gap, E g = 1.04 eV. A remarkable decrease in energy band gap is observed which is due to the structural phase transition (from cubic to orthorhombic) at 75 ºC bath temperature. Cubic and orthorhombic SnS films have electrical resistivity ρ  ≤ 2.123 × 10 3 Ω.cm. Bath temperature is observed to play an important role in tailoring the crystal structure and energy band gap of chemically bath deposited tin sulfide thin films. Results suggest that the tin sulfide films can be deposited with required combination of properties for optical and energy harvesting devices. graphical Abstract: ga1 Highlights: Tin sulfide thin films are prepared by chemical bath deposition. Effect of bath temperature on the structural and optical properties is studied. Cubic to orthorhombic phase transition is observed at 75 °C bath temperature. Optical properties are remarkably affected due to phase transition.